Application of fuzzy logic in an optimal PWM based control scheme for a multilevel inverter - Azli, N. A. (2003)

(untitled)
Various circuit topologies and control techniques have been proposed on inverters for AC power supply applications but without much emphasis on very high power systems. Incorporation of a non conventional inverter topology known as multilevel inverter with an optimal PWM based control scheme is proposed in this work for high voltage applications when the switching frequency of the inverter power devices is limited by the maximal power loss. A Fuzzy Proportional Integral Controller (FPIC) takes a role in the control scheme in providing stronger control action far a large voltage error and a smoother control action {or a small voltage error in the multilevel inverter output. This in turn ensures that high quality output voltage at a fixed frequency is always maintained on the inverter output while the transient response improved regardless of the loading conditions. This paper focus on the development of this control scheme which is supported by some results based on a simulation study.